Anti-Pentraxin Antibodies in Autoimmune Diseases: Bystanders or Pathophysiological Actors? - Brilland, Benoit; Vinatier, Emeline; Subra, Jean-François; Jeannin, Pascale; Augusto, Jean-François; Delneste, Yves (Frontiers in Immunology, 2021)
Pentraxins are soluble innate immunity receptors involved in sensing danger molecules. They are classified as short (CRP, SAP) and long pentraxin subfamilies, including the prototypic long pentraxin PTX3. Pentraxins act mainly as bridging molecules favoring the clearance of microbes and dead cells. They are also involved in many other biological processes, such as regulation of complement activation, inflammation and tissue homeostasis. Autoantibodies directed against pentraxins have been reported in various autoimmune diseases, especially in systemic lupus erythematosus and ANCA-associated vasculitis. In this review, we review the main biological characteristics and functions of pentraxins and summarize data concerning autoantibodies directed against pentraxins in the context of autoimmune diseases and discuss their potential pathological role.